STRATEGI KEPALA SEKOLAH MEMBANGUN PARTISIPASI MASYARAKAT UNTUK EKSISTENSI SEKOLAH - Nurita, Ita; Mahmud, M. Eka; Salehudin, Mohammad (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
Schools located in urban areas appear to be advanced and at the forefront because they are supported by development facilities and the existence of advanced government and communities, so it is easy to encourage community participation and their existence to be advanced and superior, but it is very different from schools in rural areas that require the figure and strategy of the principal as a leader, relationship community to build community participation to support the existence of schools. The purpose of this study is to describe the principal's strategy to build community participation as an effort to school existence. This study uses a descriptive qualitative approach, the authors go directly to conducting interviews. Interviews to explore primary data and analyzed using Miles and Huberman, models. The results of the study found that the principal's strategy as a leader as well as public relations was by (1) the new school year holding work meeting or working meeting, (2) visiting parents' homes to convince the community and parents of students. (3) by using influential public figures. (4). provide opportunities for the community to participate, (5). carry out publications and socialization through TV and school channels, (6). overcome various obstacles and barriers to schools involving the community. Meanwhile, community participation in SMP IT Insan Cendikia Kutai Kartanegara is (1) Participation in the form of money and goods; Participation in the form of funds and goods by parents and the community with an awareness of education. (2) Participation of personnel and expertise; in the form of personnel who come from several guardians of students with certain skills and professions such as doctors, chefs, soldiers, police, entrepreneurs, farmers, and breeders. (3). Thought participation; community participation in the form of thoughts and policies in schools.